The queen of the valley - Hughes, Lorena (Kensington Publishing Corp., 2023)
"Driven and recklessly daring, Martin Sabater follows his lifelong dream of owning a cacao plantation in Valle del Cauca. But on the night of a spectacular gala, he disappears--and is never seen again. Now his hacienda is a budding Catholic hospital saving lives during an emerging epidemic. And novice nun "Sor Puri" is there to uncover the truth behind Martin's disappearance. But her real identity--and her past with the heartbreakingly charismatic Martin--will put far more than her perilous search at risk. A professional photographer, Lucas Ferreira is Martin's best friend since boyhood. He has his own reasons for helping the determined, alluring nun. But what this reserved man won't reveal about his thwarted dreams and unrequited passion could prove key to the past--or a lethal trap. Martin was head nurse Sor Camila's only love--until an unfortunate mistake changed the course of her life forever. Now, Martin's home is an unexpected chance for her, Lucas, and Puri to set the past right. But with their secrets unearthing explosive memories and wrenching lies, can they survive the truth about Martin--and the consequences that will forever alter their destinies?"--